Vincamine induces cytoprotective autophagy via regulation of ampk/mtor signaling pathway in gentamicin-induced hepatotoxicity and nephrotoxicity in rats - Alaa Abouelhamd; Nourhan Elpry Mahmoud Shehata; Sara Mohamed Naguib Abdel-Hafez; Dalia H. Abu-Baih (Scientific Reports)
Abstract Gentamicin (GET), a widely utilized aminoglycoside antibiotic for severe bacterial infections, is associated with significant hepatorenal toxicity. These adverse effects are frequently exacerbated by GET-induced oxidative stress and inflammation. This study aimed to evaluate the potential protective efficacy of vincamine (VIN) against GET-induced hepatic and renal damage. 4 groups of adult male rats were assigned: normal control (received CMC), GET (100 mg/kg, i.p.), VIN (40 mg/kg, p.o.), and GET/VIN (received both VIN and GET) for 7 days. Liver and kidney function tests were performed. Serum total antioxidant capacity (TAC) and tissue malondialdehyde (MDA) were quantified. To assess apoptosis, Bax and Bcl-2 mRNA levels were quantified using real-time polymerase chain reaction (RT-PCR), while cleaved caspase-3 protein levels were measured using ELISA. Histopathological alterations were also examined. The implication of autophagy was assessed by detecting AMPK, beclin-1, LC3 and mTOR proteins. Our results indicated that VIN significantly attenuated GET-induced hepatotoxicity and nephrotoxicity by mitigating oxidative stress and apoptosis. Mechanistically, VIN modulated apoptotic pathways by upregulating the anti-apoptotic Bcl-2 gene and downregulating the pro-apoptotic Bax gene. Notably, VIN potently enhanced autophagy through modulation of the AMPK/mTOR signaling pathway, evidenced by the upregulation of beclin1 and LC3 levels. Histopathological analysis further corroborated these findings, demonstrating that VIN markedly reduced the tissue damage associated with GET administration. VIN demonstrates potential as a cytoprotective agent against GET-induced hepatorenal toxicity. The protective effect of VIN may be attributed to its capacity to modulate the Bax/Bcl-2/Caspase-3-dependent apoptotic pathway and the AMPK/mTOR-mediated autophagy pathway.